2014
DOI: 10.1136/vr.102189
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of corneal anaesthesia after the application of topical 2 per cent lidocaine, 0.5 per cent bupivacaine and 1 per cent ropivacaine in dogs

Abstract: The objective of this study was to describe and compare the efficacy and duration of topical anaesthesia induced by 2 per cent lidocaine (L), 0.5 per cent bupivacaine (B) and 1 per cent ropivacaine (R) in the dog using 24 clinically healthy beagles with normal ocular examination. Dogs were randomly divided into three groups: 2 per cent lidocaine (n=8), 0.5 per cent bupivacaine (n=8) and 1 per cent ropivacaine (n=8). The baseline corneal touch threshold (CTT) was measured using a Cochet-Bonnet aesthesiometer. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…) supports those conclusions, and it is recommended that environmental conditions be reported when evaluating corneal sensitivity in an effort to standardize data. For example, in a study of dogs from Barcelona, Spain baseline corneal sensitivity was reported as 40 mm while a similar study in Toulouse, France reported a baseline of 15 mm. Both locations are similar in latitude and longitude, but vastly different weather conditions may exist during similar parts of the year.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…) supports those conclusions, and it is recommended that environmental conditions be reported when evaluating corneal sensitivity in an effort to standardize data. For example, in a study of dogs from Barcelona, Spain baseline corneal sensitivity was reported as 40 mm while a similar study in Toulouse, France reported a baseline of 15 mm. Both locations are similar in latitude and longitude, but vastly different weather conditions may exist during similar parts of the year.…”
Section: Discussionmentioning
confidence: 65%
“…For instance, the lowest humidity in Barcelona occurs during February, while in Toulouse, this occurs during the end of July . The authors of the Barcelona and Toulouse studies confirmed the timeframe in which the experiments were performed. Interestingly, the Toulouse study was performed during higher humidity conditions, which may explain the vast difference in corneal sensitivity values reported compared to those obtained in Barcelona.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The sample size was deduced from previous similar studies, which showed a rather heterogeneous sampling size: i.e. 8 [beagles, [17]], 9-10 [rats, dogs, [16]], 12+12 [cows, [11]], 12-22 [dogs, [5]], 18 [cats, [9]], 20 [cats, [18]]. In addition, this sample size resulted in an attempt to conform with the guiding principles for the ethical use of animals in testing ("The Three Rs").…”
Section: Animalsmentioning
confidence: 99%
“…Most of these research studies assessed the effectiveness of ropivacaine for peribulbar anesthesia and as a topical agent in cataract surgery. Few studies have investigated its effect on corneal sensitivity [17,31], and, to the author's knowledge, no similar study was performed out in rats.…”
Section: Plos Onementioning
confidence: 99%